Production of cellulase from oil palm biomass as substrate by solid state bioconversion - Alam, Md. Zahangir; Muhammad, Nurdina; Mahmat , Mohd Erman (Science Publications, 2005)
Solid state bioconversion (SSB) of lignocellulosic material oil palm biomass (OPB) generated from palm oil industries as waste was conducted by evaluating the enzyme production through filamentous fungus in lab-scale experiment. OPB in the form of empty fruit bunches (EFB) was used as the solid substrate and treated with the fungus Trichoderma harzianum to produce cellulase. The results presented in this study revealed that the higher cellulase activity of 0.0413 unit was achieved at the day 3 of fermentation. While the optimum study indicated the enzyme production of 0.0433 unit with moisture content of 50%, 0.0413 unit with 5% v/w of inoculum size and 0.0413 unit with co-substrate concentration of 2% (w/w) at days 9, 9 and 12 of fungal treatment, respectively. The parameters glucosamine and reducing sugar were observed to evaluate the growth and substrate utilization in the experiment.